Web-Based Inventory System at PT Bringin Karya Sejahtera with Waterfall Method - Lubis, Jelita Ananda; Zulfahmi Syahputra; Hanna Willa Dhanny (Bahasa Indonesia, 2026)
PT Bringin Karya Sejahtera is a company engaged in services and facility management and requires an integrated inventory system that operates effectively. Inventory management, which is still carried out manually or semi-computerized, often causes various issues, such as discrepancies in stock quantities, delays in report preparation, and difficulties in monitoring and controlling items. Based on these problems, this study aims to design and develop a web-based inventory system capable of supporting more accurate, fast, and efficient data management of items. The development method applied in this study is the Waterfall model, which includes stages of requirements analysis, system design, implementation, testing, and maintenance. The system is built using a web-based programming language with centralized database support, allowing it to manage incoming and outgoing goods, stock inventory, and generate reports automatically and in real-time. The result of this research is a web-based inventory system that can improve inventory management effectiveness, reduce the potential for recording errors, and facilitate monitoring and reporting processes. With the implementation of this system, inventory management at PT Bringin Karya Sejahtera is expected to become more systematic, transparent, and efficient.